Prevalence and Signal Detection of Adverse Drug Events from Inappropriate Sources in the Community: an Analysis of Reports in the Thai Databases on Adverse Drug Events (Thai Vigibase) - Puripunyavanich, Naphaphorn; Saokaew, Surasak (Journal of Health Science of Thailand, 2024)
Self-medication from inappropriate drug sources in the community can result in adverse events (AEs) that require hospitalization. Previous studies are not nationwide studies on the magnitude of the problem and risk. We conducted a retrospective descriptive study using data from spontaneous AE reports in the Thai Vigibase for 2021–2022 to analyze the national level of the prevalence of AEs from drugs received from inappropriate drug sources and assessed the signals detection for risk of severe AEs in three target drug groups: non-steroidal anti-inflammatory drugs (NSAIDs), steroids, and antibiotics. The data were analyzed using descriptive statistics, encompassing numbers and percentages. Additionally, reporting odds ratios and 95% confidence intervals were calculated to assess risk signals. By using the STATA/IC version 14.0, we could make an analysis, which revealed that the number of AEs stemming from inappropriate drug distribution sources in 2021 and 2022 was 279 out of a total of 136,453 events and 295 out of a total of 99,642 events, respectively. Grocery stores were the most common inappropriate source of drug distribution, accounting for 75.27 percent of AEs in 2021 and 72.88 percent in 2022. The top three drug groups that caused the most AEs in both years were anti-inflammatory and anti-rheumatic products, systemic antibiotics, and analgesics, respectively. The top three drugs with the most AEs in both years were NSAIDs and antibiotics, namely piroxicam, tetracycline, and diclofenac. The prevalence of AEs from all drugs received from inappropriate drug sources in 2021 and 2022 was 0.20 and 0.30, respectively. The prevalence of the target drug groups to be monitored, namely NSAIDs, antibiotics, and steroids, in 2021 was 0.009, 0.004, and 0.003, respectively, and in 2022 it was 0.013, 0.004, and 0.03, respectively. NSAIDs were the only drug group with risk signals for severe AEs in both years, and diclofenac was the only drug with risk signals in 2021. The findings of this study can serve as baseline information for monitoring and evaluating the implementation of the Ministry of Public Health’s guidelines for the rational use of medicine in communities. Furthermore, Risk management measures should be established at both national and local levels to address the issue of NSAIDs and diclofenac, which display signs of serious AEs. All hospitals should establish a proactive drug safety surveillance system with rational drug use guidelines to ensure the availability of high-quality data to Thai Vigibase.